Pathology and Advanced Imaging—Characterization of a Congenital Cardiac Defect and Complex Hemodynamics in a Pig: A Case Report - Malbon, Alexandra J.; Weisskopf, Miriam; Glaus, Lukas; Neuber, Sebastian; Emmert, Maximilian Y.; Stoeck, Christian T.; Cesarovic, Nikola (Frontiers in Veterinary Science, 2021)
Domestic pigs are widely used in cardiovascular research as the porcine circulatory system bears a remarkable resemblance to that of humans. In order to reduce variability, only clinically healthy animals enter the study as their health status is assessed in entry examination. Like humans, pigs can also suffer from congenital heart disease, such as an atrial septal defect (ASD), which often remains undetected. Due to the malformation of the endocardial cushion during organ development, mitral valve defects (e.g. mitral clefts) are sometimes associated with ASDs, further contributing to hemodynamic instability. In this work, we report an incidental finding of a hemodynamically highly relevant ASD in the presence of incompetent mitral and tricuspid valves, in an asymptomatic, otherwise healthy juvenile pig. In-depth characterization of the cardiac blood flow by four-dimensional (4D) flow magnetic resonance imaging (MRI) revealed a prominent diastolic left-to-right and discrete systolic right-to-left shunt, resulting in a pulmonary-to-systemic flow ratio of 1.8. Severe mitral (15 ml/stroke) and tricuspid (22 ml/stroke) regurgitation further reduced cardiac output.. Pathological examination confirmed the presence of an ostium primum ASD and found a serous cyst of lymphatic origin that was filled with clear fluid partially occluding the ASD. A large mitral cleft was identified as the most likely cause of severe regurgitation, and histology showed mild to moderate endocardiosis in the coaptation area of both atrio-ventricular valves. In summary, although not common, congenital heart defects could play a role as a cause of experimental variability or even intra-experimental mortality when working with apparently heathy, juvenile pigs.